Numerical simulation of supersonic subsea compact wet gas separator for gas transmission pipeline - Hashim, F.M. (Trans Tech Publications Ltd, 2014)
Conventional wet gas separators are used as a means to remove free water using the gravitational settling and momentum principle. However, these separators possess setback in terms of its efficiency. Alternatively, supersonic compact wet gas separators have been designed in Universiti Teknologi PETRONAS Gas Separation Research Center (UTPGSRC) which uses supersonic flow to separate natural gas and free water. In its preliminary design, determination of the flow behavior according to the design of the separators is important. The result provides information whether the design can be accepted or improvement should be taken into consideration. It is therefore an objective of this paper to numerically simulate and analyze the flow characteristic such as velocity, pressure and temperature distribution correlating with the separator design. From the flow performance results obtained, it shows that the separator design has fulfilled the requirement. Â© (2014) Trans Tech Publications, Switzerland.